Avaliação de um programa de práticas educativas para monitoras de um abrigo infantil - Prada, Cynthia Granja (2007)
In the last few decades, it seems to be increasing the number of families who find difficulties to educate its children. The most frequent parents concerns are: the difficulty of establishing limits to the behavior of the child or adolescent; how to develop behaviors that they believe to be right; and how to proceed when behaviors problems appears. These difficulties do not restrict to the universe of the families who take care of its own children, but they are also focus of concern on institutions that foster care children victims of domestic violence and those caregivers. The lack of preparation of parents, educators or caregivers of institutions, many times may develop or aggravate problems of development and behavior of these children. For this reason, this study had the aim to develop, implement and evaluate a program of intervention with caregivers that work with sheltered children who had been victims of domestic violence, in order to present a reference on Educative practices, preventing or reducing possible behavior problems of these children. To evaluate the effectiveness of the intervention program, evaluations had been applied before the beginning (pre-test) of the intervention program and soon after its ending (postest), using the following instruments: IEP - Inventory of Educative Practices, CBCL - Child Behavior Checklist and the Script of interview of life and professional background of the caregivers. Also were collected continuous measures of the Interaction between the caregivers and the children in 19 sessions, defined as 3 of base line, 12 taken three days after each Intervention session and 4 of follow-up, applied five months after the ending of the intervention. The results demonstrated a significant reduction of the negative educative practices, mainly in Relaxed Disciplines and Negative Monitoring, with high scores at the pre-test, as well an increase of the positive educative practices. The evaluation using the CBCL demonstrated that the children had presented statistical significant behavior improvement. The continuous measures data had indicated an increase of positive interaction behaviors between caregivers and children, as well a reduction of negative interaction behaviors, and the most significant outcome was that the measured frequencies of good behaviors in follow-up sessions did not return to the measured levels of the base line. The considered intervention program presented can be considered efficient to generate changes in the interaction standards between caregivers and children; however it would need to be applied in different institutions to assure the applicability in distinct environments.